Pacing and placing in 161-km ultramarathons: Effects of sex and age - Shawn E. Bearden; Irene van Woerden (PLoS ONE, 2025)
Ultramarathons are growing in popularity, owing especially to the participation of women and masters athletes. Pacing strategy, which can vary by sex and age, is a critical variable in determining finishing place in races up to the marathon distance. Whether this is true in 161-km ultramarathons is unclear. We tested the hypotheses that pacing is a determining factor in finishing place and that pacing differs by sex and age in 161-km ultramarathons. Publicly available data from 161-km races (n = 6) were analyzed for years 2012–2022 (n = 56). Linear regression was used to analyze the proportion of time in each segment (between timing checkpoints) by place, sex, and age. In general, runners used the same percentage of their total race time in each segment independent of finishing place, sex, or age. The exception was that later finishers often ran proportionally faster at the start compared to earlier finishers. Finishing times increased with age but pacing was unaffected by age or sex. We conclude that slower finishers paced the same as faster finishers following a relatively quick start in these ultramarathons, and pacing was not consistently affected by sex or age. These findings should inform training decisions and racing strategy in 161-km ultramarathons.